Unintended consequences of the Home Affordable Refinance Program - Phoebe Tian; Chen Zheng (Bank of Canada, 2024)
We study the unintended effects of the Home Affordable Refinance Program (HARP) on mortgage borrowers. Originally designed to help financially distressed borrowers refinance after the 2008-09 global financial crisis, HARP inadvertently amplified the market power of incumbent lenders by introducing a cost differential between incumbents and their competitors. To assess the welfare implications of this cost advantage, we develop and estimate a structural model of dynamic refinancing decisions with lenders' offers arising from a search and negotiation process. Our findings reveal that although the cost asymmetry was rectified by a 2013 policy, it still resulted in a welfare loss exceeding the impact of search frictions.
Keywords: G21; G51; L51; 330; Financial institutions